2020
DOI: 10.1159/000505700
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Life or Rechargeable Battery for Deep Brain Stimulation: A Prospective Long-Term Study of Patient’s Preferences

Abstract: <b><i>Introduction:</i></b> Deep brain stimulation (DBS) is an established treatment for movement disorders. We have previously shown that in our practice, the majority of adult patients prefer fixed-life implantable pulse generators (IPGs), although rechargeable batteries are increasingly used. The aim of this study was to evaluate patients’ long-term satisfaction with their choice of battery and factors that influence their decision. <b><i>Methods:</i></b> Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Furlanetti et al reported that the main reasons for choosing the nr-IPG were convenience and concern about forgetting to recharge; however, patients using r-IPG did not report experiencing this problem (18). In our study, the main reason for choosing an nr-IPG was the economic cost (92% of patients with nr-IPGs and 62% of patients with r-IPGs).…”
Section: Discussionmentioning
confidence: 50%
“…Furlanetti et al reported that the main reasons for choosing the nr-IPG were convenience and concern about forgetting to recharge; however, patients using r-IPG did not report experiencing this problem (18). In our study, the main reason for choosing an nr-IPG was the economic cost (92% of patients with nr-IPGs and 62% of patients with r-IPGs).…”
Section: Discussionmentioning
confidence: 50%
“…Most studies have focused on DBS safety and efficacy, but the patient's perspective on the DBS treatment delivered and the reasons for choosing or accepting a specific DBS system remain an important but under-recognized topic. For example, only a few studies performed in Europe have demonstrated that patients with PD preferred rechargeable IPG batteries over fixed-life batteries (7)(8)(9). This situation is problematic because patient preference and satisfaction are important for treatment acceptance, treatment compliance, and the further development of next generation of DBS systems.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the non-rechargeable IPG showed a lower score on satisfaction than the size of the rechargeable IPG. Furlanetti et al [10] concluded that the concern about IPG size in patients that received a non-rechargeable IPG rose from 6.7% preoperatively to 60% on long-term postoperative follow-up. Size could be a determining factor, especially in patients with IPG discomfort, pocket pain, or low BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor in the choice of IPG may be national or center-specific agreements on reimbursement [9]. Besides financial and technical reasons, motor and cognitive functions, patient capability to monitor and operate the device, the size of the IPG [10], and patient preference may be determining factors. The complexity of IPG choice is increased further by combining implants from different medical device manufacturers to enable new stimulation options with already implanted DBS electrodes by creating so-called hybrid DBS systems [11,12].…”
Section: Introductionmentioning
confidence: 99%